Stereotactic body radiation therapy for spine and non-spine bone metastases. GETUG (french society of urological radiation oncologists) recommendations using a national two-round modified Delphi survey. (November 2022) - Vilotte, F.; Pasquier, D.; Blanchard, P.; Supiot, S.; Khalifa, J.; Schick, U.; Lacornerie, T.; Vieillevigne, L.; Marre, D.; Chapet, O.; Latorzeff, I.; Magne, N.; et al.
Abstract: Backround and purpose: The relevance of metastasis-directed stereotactic body radiation therapy (SBRT) remains to be demonstrated through phase III trials. Multiple SBRT procedures have been published potentially resulting in a disparity of practices. Therefore, the french society of urological radiation oncolgists (GETUG) recognized the need for joint guidelines for metastasis-directed SBRT in order to standardize practice in trials carried out by the group. Materials and methods: After a comprehensive litterature review, 97 recommandation statements were created regarding planning and delivery of spine bone (SBM) and non-spine bone metastases (NSBM) SBRT. These statements were then submitted to a national online two-round modified Delphi survey among main GETUG investigators. Consensus was achieved if a statement received ≥ 75 % agreements, a trend to consensus being defined as 65–74 % agreements. Any statement without consensus at round one was re-submitted in round two. Results: Tweny-one out of 29 (72.4%) surveyed GETUG investigators responded to both rounds. Consensus was achieved for 91/97 statements (93.8%) allowing the edition of comprehensive guidelines encompassing all aspects of SBM and NSBM SBRT planning and delivery: patients selection (19 statements), treatment preparation (14 statements), target volume delineation (18 statements), dose and fractionation (11 statements), prescription and dose objectives (9 statements), organs at risk dose constraints (15 statements) and image guided radiation therapy (11 statements). Conclusion: GETUG guidelines for SBM and NSBM SBRT were agreed upon using a validated modified Delphi approach. These guidelines will be used as per-protocol recommendations in ongoing and further GETUG clinical trials.